Implicaciones Socio-ambientales del Conflicto en Colombia - Moreno Medel, Martha Inés (2018)
The conflict has generated devastation, forced displacement, unemployment and even food crisis; Solutions are being sought through the peace talks, but these at the same time create other type of conflict because displaced people and workers with limited resources are not going to have the same benefits, which generates inequity. Education should be based on the construction of the triadic brain tetra-level (three predominances in four levels of development); using training programs that use as a base the skills development of the triadic brain; Nowadays each brain predominance looks for their own benefit and it is needed to dissolve some knowledge to be able to have a mentality change, where everyone that has been a victim in conflict is able to empathize with their opponents in search of general welfare, survival in decent conditions and the planet conservation¸ studies and the implemented strategies so far have been from the point of view of the traditional curriculum. In conflict the main factor is the human being; it is unsustainable for peace to last if we don’t face the process to dissolve some knowledge and learn something new from the integral brain: the left logical predominance where all the peace talks have come from, the right one to develop the affective, creative part of the environment and the central reptilian predominance where survival is located. Agroecology forms an innovative tridimensional trend to implement (Science, Practice, Social Movement and/or Political), where the changes of scientific and technologic paradigms act and work in constant reciprocity to achieve a social impact.